How Crop Intensification and Diversification Changes Farmers' Livelihoods in Northern Bangladesh: An Impact Study - Humaira Sadaf, Bushra; Haque, Abdul; Miajy, Abdullah; Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2024)
Agriculture is the backbone of Bangladesh, contributing 13% to the country’s GDP and ensuring food security for millions. Rice, the staple food and primary source of calories dominates the agricultural landscape, with 75% of cultivable land dedicated to its production. However, rice monocropping—particularly long-duration Aman rice—limits farmers' ability to diversify and intensify their land’s potential, leaving fields fallow between two rice crops.